Endoscopic Doppler Probe in the Diagnosis and Management of Upper Gastrointestinal Hemorrhage. Issue 1 (2018) - Satyavada, Sagarika; Davitkov, Perica; Ali, Meer Akbar; Cooper, Gregory; Wong, Richard C. K.; Chak, Amitabh
ABSTRACT : N/A: Through‐the‐scope (TTS) endoscopic Doppler ultrasound probe technology is a tool that has garnered interest for the evaluation of variceal and non‐variceal bleeding. In previous studies, this technology has been proposed as a more objective method of identifying the bleeding subsurface blood vessel in peptic ulcer hemorrhage. We describe 3 cases where the use of an endoscopic Doppler probe guided the diagnosis and management of upper gastrointestinal (GI) hemorrhage due to causes other than peptic ulcer disease. The first case describes a patient with a duodenal Dieulafoy lesion, while the other 2 cases outline patients with a gastroesophageal varix as the etiology of the bleed.